The role of product cues and regulatory focus in the consumers’ response to green products: The mediation effects of green attitudes - Wang, Xiaomei; Gu, Yangli; Xin, Haohang; Qiu, Peiling; Wang, Jia (Frontiers in Psychology, 2022)
By applying the cue diagnosticity theory, this study explores the influence mechanism of consumption response to low-involvement products and high-involvement products, respectively. Specifically, the purpose of this study is to investigate how product clues(brand strength and retailer reputation) affect consumption responses to green products with different involvement, and to examine regulatory focus as a moderator and green attitude as a mediator. The results of study 1 reveal that for low-involvement green products, the effect of the retailer reputation rather than brand strength on consumption response is mediated by a green attitude, and regulatory focus plays a moderating role in this process. The results of study 2 show that for high-involvement green products, the effect of the brand strength rather than retailer reputation on consumption response is mediated by a green attitude, however, regulatory focus does not play a moderating role in this process. Finally, the data aggregation verifies that people's consumption response to green products strongly depends on the retailer reputation, brand strength and green attitude, and there is a moderated mediation effect of regulatory focus on the indirect effect of retailer reputation(rather than brand strength) on consumption response via green attitude. As behavioral antecedents differ across the analyzed product types in forming consumer response, it is very important for policymakers and marketers to take note of the differences when designing marketing activities for green products.